2021
DOI: 10.1002/crat.202100012
|View full text |Cite
|
Sign up to set email alerts
|

Amylopectin Regulated Mineralization of Calcium Carbonate and Its Application in Removing of Pb(II)

Abstract: As an ecological and environment-friendly building material, sticky rice mortar has attracted the attention of many researchers. Amylopectin is the most important organic matter of it, which can improve the mechanical properties and durability of sticky rice mortar by inducing mineralization of calcium carbonate ( CaCO3 ). However, amylopectin induced formation of CaCO 3 has not been reported. In this paper, mineralization of CaCO 3 induced by gelatinized amylopectin is investigated. For comparison, the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…24 b). In the field of water treatment, gelatinized amylopectin-induced mineralization of CaCO3 was performed, and the produced CaCO 3 , when used for water purification Pb(II) adsorption, was found to be extremely high [284]. CaCO 3 can as such, be used for heavy metal adsorption from water; however, natural calcite has a very low heavymetal adsorption efficiency.…”
Section: Artificial Carbonate Structuresmentioning
confidence: 99%
“…24 b). In the field of water treatment, gelatinized amylopectin-induced mineralization of CaCO3 was performed, and the produced CaCO 3 , when used for water purification Pb(II) adsorption, was found to be extremely high [284]. CaCO 3 can as such, be used for heavy metal adsorption from water; however, natural calcite has a very low heavymetal adsorption efficiency.…”
Section: Artificial Carbonate Structuresmentioning
confidence: 99%
“…The following research discovered that dextran could effectively induce leaf-like aragonite crystals when used as a template [27]. Zhao et al [28] studied calcium carbonate induced by amylopectin, Mg 2+ , and Fe 3+ . The results showed that amylopectin was instrumental in forming pumpkin-like calcite, while rod-like and dumbbell-like calcite were formed in the presence of Mg 2+ , and calcite with step depression was formed in Fe 3+ .…”
Section: Introductionmentioning
confidence: 99%